(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Bones and joint disorders are common in the working age population and are conditions that affect passive (bones, joints) and/or active structures of the body (muscles, tendons, ligaments, peripheral nerves) . A 35 year old moderately built young gentle man working as an IT professional, complains of pain on nape of neck and back of the chest since one year. But however pain started radiating to left upper arm since past 4 months, night starts which apparently effecting sleep. Pain gets aggravated by physical activities like continuous sitting posture and gets relieved by analgesics and sleep at Chondroitin Sulphate. Cervical IVDP, can be considered as Apabahuka or Asthi majjagata vata . He was managed with external and internal medications like cervical traction, Lepanam, physio, Gandharvahasthadi kashayam, Sneha panam done with Gugguluthikthakam ghee, purgation done with Gandharvahasthadi erandam and Nasya done with Anutailam and Ksheerabala tailam